Spanish Language Education in the United States: Beginning, Present, and Future. - Pentón Herrera, Luis Javier (Íkala, Revista de Lenguaje y Cultura, 2018)
Language instruction and learning was an innate part of early educational programs in the United States. Among the most common languages taught at schools and universities were Latin, Greek, German, and French; however, Spanish was not formally taught at an American institution until 1749. Since then, the works of important scholars such as Mariano Cubí y Soler have provided the foundation for the success of the Spanish language in the United States. Today the Spanish language is thriving in the U.S. as it is considered the foreign language most commonly taught. Furthermore, by the year 2050 the United States is expected to have more Spanish speakers than any other country in the world. This literature review offers a historical analysis of the Spanish language instruction in the United States since its beginnings in the XVIII century to present. In addition, it offers information about the trends, methodologies and approaches used to teach Spanish throughout the years and offers an insight to possibilities of future research.